Guimarães Rosa und Meyer-Clason Literatur, Demokratie, ZusammenLebenswissen - Ette, Ottmar; Astor Soethe, Paulo (MIMESIS, 2020)
This edited volume, which features essays from prominent German, Brazilian, and Portuguese scholars, deals with the personal relations and intensive intellectual collaboration between Joao Guimaraes Rosa (1908-1967) and his German translator Curt Meyer-Clason (1910-2012), a special case of German-Brazilian cultural exchange.